The burden of motor neuron diseases in Asia, 1990–2021: temporal patterns and age-period-cohort analyses - Shi, Tianyu; Qian, Zhiheng; Liu, Tao; Zhang, Peng (Frontiers in Neurology, 2025)
BackgroundThis study aims to characterize the temporal trends of motor neuron diseases (MNDs) burden in Asia from 1990 to 2021, estimate their age, period and cohort effects, and forecast the disease burden for the next 15 years.MethodsData were obtained from the Global Burden of Disease study 2021. The average annual percentage change (AAPC) of MNDs incidence, prevalence, mortality and disability-adjusted life years (DALYs) in Asia from 1990 to 2021 were estimated by joinpoint regression analysis. Age, period and cohort effects on incidence and mortality of MNDs were also evaluated by the age-period-cohort analysis. The autoregressive integrated moving average model was used to forecast age-standardized incidence, prevalence and mortality rates of Asian MNDs in 2022–2036.ResultsFrom 1990 to 2021, the age-standardized mortality and prevalence rates of Asian MNDs increased from 0.140 to 0.173/100,000, and from 2.134 to 2.187/100,000, respectively. While the age-standardized incidence rate in Asia decreased from 0.561/100,000 in 1990 to 0.478/100,000 in 2021. The AAPC in age-standardized incidence, prevalence, mortality and DALYs rates of MNDs in Asia were −0.508, 0.087, 0.649 and −0.045, respectively. The age-period-cohort analysis showed that, for mortality and incidence, the burden of MNDs increased with age. The period effect exhibited an initial decline followed by a subsequent resurgence. The cohort effect increased in the early birth cohort while declined in the recent birth cohort. By 2036, the prevalence and mortality of MNDs are projected to rise to 2.241/100,000 and 0.177/100,000, respectively, while incidence is projected to decline to 0.468/100,000.ConclusionsThe age-standardized incidence rate of MNDs in Asia was reduced yet their age-standardized rates of prevalence and mortality increased. This trend is projected to persist into the foreseeable future. Given substantial population base and increasingly severe aging demographics in Asia population, a holistic strategy is required to ease the burden of MNDs in Asia and get better health results for Asian patients with MNDs.